2023
DOI: 10.1002/anie.202306877
|View full text |Cite
|
Sign up to set email alerts
|

Pure and Metal‐confining Carbon Nanotubes through Electrochemical Reduction of Carbon Dioxide in Ca‐based Molten Salts

Abstract: To be successfully implemented, an efficient conversion, affordable operation and high values of CO 2 -derived products by electrochemical conversion of CO 2 are yet to be addressed. Inspired by the natural CaO-CaCO 3 cycle, we herein introduce CaO into electrolysis of SnO 2 in affordable molten CaCl 2 -NaCl to establish an in situ capture and conversion of CO 2 . In situ capture of anodic CO 2 from graphite anode by the added CaO generates CaCO 3 . The consequent coelectrolysis of SnO 2 and CaCO 3 confines Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…37 The nucleation and growth mechanism of CNT induced by Fe 2 O 3 /Co@C was further validated by the successful generation of high-quality FeCo nanoparticles via the Fe/Co nucleus. 38 Fe/Co appeared to be doped into the grown walls of CNTs in the presence of N (Fig. 1g).…”
Section: Resultsmentioning
confidence: 99%
“…37 The nucleation and growth mechanism of CNT induced by Fe 2 O 3 /Co@C was further validated by the successful generation of high-quality FeCo nanoparticles via the Fe/Co nucleus. 38 Fe/Co appeared to be doped into the grown walls of CNTs in the presence of N (Fig. 1g).…”
Section: Resultsmentioning
confidence: 99%
“…The potential decreased with time, eventually reaching a potential lower than 0 V at which metal electrodeposition proceeded. From the report that CaC 2 tends to form at potentials lower than Ca electrodeposition, 25 the reaction to form metal carbide was considered to have proceeded even at potentials lower than 0 V. The current efficiencies for C 2 H 2 gas generated by the reaction between the obtained samples and water (Figure 5b) were estimated to be 34% for NaCl−KCl− CaCl 2 −CaO system without CaC 2 and 68% for that with CaC 2 . The results indicated that the addition of CaC 2 into the melt enhanced the current efficiency because of the suppression of the dissolution of electrodeposited CaC 2 in the melt.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that the carbon nanotube was formed through the mediation of CaC 2 in molten CaCO 3 −Na 2 CO 3 −K 2 CO 3 at 1073 K using a Ni-sheet cathode. 25 The acetylene gas can be produced by the reaction between the metallic carbides with water. In the conventional process, the CaC 2 is industrially manufactured by heating a mixture of quicklime and coke to about 2000 °C in an electric furnace.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, metals such as Ge, Sn, Zn, and Fe have been introduced to CO 2 -C to synthesize metal@CNTs or metal@carbon spheres through the coreduction of CO 2 and metal oxides (GeO 2 , SnO 2 , ZnO, and FeO) or utilization of a liquid zinc anode, thereby enhancing the LIBs' performance. 14,34,35 Regarding the applications of electrocatalysts, there have been few reports on employing metal-free CO 2 -C as electrocatalysts. To date, only approximately two studies have concentrated on its application in the two-electron (2e) oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%